Fintech Syariah Di Masa Depan : Peluang Dan Tantangan - Rika Nur Amelia; Muhammad Afiqul Rifqi; Muhammad Afton Ilman Huda; Eny Latifah (Universitas 45 Surabaya, 2024)
This article aims to explore the future of Islamic fintech with a focus on the opportunities and challenges facing the industry. The research endeavors to provide a comprehensive understanding of how Islamic fintech can develop and compete in the global financial market. The study adopts a qualitative approach with a literature review method. The selection of literature sources includes academic journal articles, books, industry reports, and academic publications related to Islamic finance, financial technology, and financial regulation. The research findings indicate that Islamic fintech has significant potential for growth, especially in countries with significant Muslim populations. However, the main challenges include strict regulation, lack of financial literacy, and competition with conventional fintech. In conclusion, Islamic fintech in Indonesia has significant opportunities and challenges. The Financial Services Authority provides opportunities for Islamic fintech players to register their businesses officially, but this process is hindered by licensing requirements and minimum capital. The negative stigma associated with conventional fintech also affects public perception of Islamic fintech, while a lack of understanding of Islamic principles makes it difficult for the public to distinguish between the two types of fintech.